Family Thorectidae Bergquist, 1978. Pp. 1028-1050. In: Hooper, J.N.A. & Van Soest, R.W.M. (eds) Systema Porifera - A guide to the classification of sponges. (2 volumes) Kluwer Academic/ Plenum Publishers: New York, 1708 + xvliii. - Cook, S. de C.; Bergquist, P.R. (2002)
Thorectidae Bergquist (Demospongiae, Dictyoceratida) is divided into two subfamilies (Thorectinae, Phyllospongiinae), contammg 23 valid genera and 129 species worldwide. Thorectids range from low and encrusting to massive in growth form. They occur throughout tropical and temperate oceans but are not recorded from polar waters. They are differentiated from other members of the Dictyoceratida by their diplodal choanocyte chambers, strongly laminated skeletal fibres, and the absence of fine skeletal filaments (characteristic of Irciniidae). Thorectid genera are differentiated by the presence or absence of a cortical armour, skeletal morphologies and the characteristic growth forms of some genera.